Abnormal Capacitance Increasing at Elevated Temperature in Tantalum Capacitors with PEDOT:PSS Electrodes - Qifeng Pan; Qiao Liu; Yuanjiang Yang; Dongbin Tian (Active and Passive Electronic Components)
Due to the importance of capacitance temperature stability in precise analog circuit applications, capacitance instability at elevated temperature of 125°C was investigated in tantalum capacitors with PEDOT:PSS counter electrodes. Capacitance-voltage measurement supposed that residual ions in the PEDOT:PSS dispersion caused an accumulation of charges at the dielectric-cathode interface which contributed to an increase in the dielectric constant and resulted in the capacitance increasing at high temperature. Based on the hypothesis, water wash process was applied and capacitance dropped significantly at high temperature. This study shows that an additional water wash process is necessary to improve the capacitance temperature stability after each dispersion dip step.